Jnana Badra: Ancient Javanese Philosophy into Human and Intellectual Capital - Jaya, I Made Laut Mertha; Ilahiyah, Mar'a Elthaf; Kusuma, Emeralda Ayu (Universitas Pendidikan Ganesha, 2025)
This qualitative study uses a hermeneutic approach that explores the form and meaning of intellectual capital, particularly human capital, through the lens of Javanese philosophy Jnana Badra (light of knowledge). As the first study to apply this unique cultural perspective, this research interprets Jnana Badra as the foundation for human direction and achievement. Findings indicate that knowledge, derived from formal education and the universe, functions as an essential light guiding human life, illuminating the path to progress, and preventing suffering. The absence of this knowledge has been shown to cause stagnation and hardship. Theoretically, this study contributes to intellectual capital theory by offering a culturally embedded understanding of human capital, encouraging knowledge that transcends narrow perspectives and promoting real impact on individuals, society, and national development. This research emphasises the importance of integrating philosophical wisdom with contemporary intellectual capital discourse.